The grand strategy of Xi Jinping’s China: goals, Comprehensive national power and policies - Tomé, Luis (2022)
What are China’s goals and ambitions? What means does it use to promote its interests? And what policies and strategies does Beijing employ to accomplish its goals? In this article we seek to answer these questions by analyzing the grand strategy of Xi Jinping’s China. Regarding the analysis, it appears that the grand strategy of Xi’s China has gone too far too fast and that perhaps time and momentum are not yet on China’s side.